2021
DOI: 10.1016/j.ebiom.2021.103339
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-wide association study of COVID-19 severity with respiratory failure

Abstract: Background Patients infected with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), responsible for the coronavirus disease 2019 (COVID-19), exhibit a wide spectrum of disease behaviour. Since DNA methylation has been implicated in the regulation of viral infections and the immune system, we performed an epigenome-wide association study (EWAS) to identify candidate loci regulated by this epigenetic mark that could be involved in the onset of COVID-19 in patients without comorbiditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
114
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 67 publications
11
114
0
1
Order By: Relevance
“…To compare the decisions on vaccines of both genders, we assume that those who are willing to pay for vaccines and wait for free vaccines are Group 1, named as getting vaccines, while those who hesitate and reject vaccines belong to Group 0, named as no vaccination. Notably, a comparison of median values of vaccine decisions in both genders using the Mann–Whitney U test showed that there are no differences in the correlation within each gender ( p -value = 0.536) (see the last row of Table 3 ) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…To compare the decisions on vaccines of both genders, we assume that those who are willing to pay for vaccines and wait for free vaccines are Group 1, named as getting vaccines, while those who hesitate and reject vaccines belong to Group 0, named as no vaccination. Notably, a comparison of median values of vaccine decisions in both genders using the Mann–Whitney U test showed that there are no differences in the correlation within each gender ( p -value = 0.536) (see the last row of Table 3 ) [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SARS-CoV-2 has been found to induce changes in DNA methylation, which affect the expression of immune response inhibitory genes that could, in part, contribute to the unfavorable progression of COVID-19 [ 46 ]. Finally, it is noteworthy that a recently identified signature made of 44 variably methylated CpGs has been predictive of subjects at risk of developing worse symptoms after SARS-CoV-2 infection [ 47 ]. Interestingly, none of these newly identified CpGs overlap with those involved in the DNAmAge prediction used in this [ 20 ] or other studies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This information was correlated with TL shortening and the expression of ACE2 mRNA. It is too early to extrapolate whether relevant clinical indications may arise from this and other studies assessing the role of epigenetic changes in the COVID-19 syndrome [ 46 , 47 ]. However, a warning might be raised that sequelae of SARS-CoV-2 infection might rely on persistent epigenomic modifications, possibly underlying the presence of a COVID-19 epigenetic memory.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report comparing patients with and without sepsis of unspecified origin indicates differential methylation at genes that participate in interferon-gammamediated (IFNγ) signaling, MHCII antigen processing and presentation, immunoglobulin production, and cell adhesion pathways [47]. In a limited study of 6 patients with SARS-CoV-2 infection, 6 DMPs (not DMRs) were observed in genes that encode proteins that participate in granulopoiesis and B-lymphocyte-to-granulocyte trans-differentiation [10]; and a very recent report of a larger cohort identifies 44 CpGs in 39 genes that were differentially methylated, including genes related to interferon response to viral infections [48]. It has also been previously reported that viral infections induce aberrant methylation patterns in host cells [33,49].…”
Section: Dna Methylation In Blood Altered In Covid-19 Patientsmentioning
confidence: 99%